CULTURAL ADVANCEMENT STRATEGIES IN INDONESIA: A LITERATURE REVIEW - Murtono, Taufik; Wahyudi, Didik Bambang (Institut Seni Indoensia Surakarta, 2024)
This study aims to explore writings throughout the last five years (2020-2024) to find out how cultural advancement strategies have been practised in Indonesia. The method used is literature research with stages 1) formulating questions and protocols for inclusion and exclusion of writing data, 2) searching for qualified writings from Google Scholar and Scopus databases, 3) selecting writing data by extracting data and identifying data duplication, 4) analysing data based on the quantity and quality of writing according to theme groups, 5) presenting data in an analysis matrix, 6) interpret the results of the analysis and draw conclusions. The study results concluded that the strategy of promoting culture in Indonesia is carried out through legal policy, social and cultural innovation, and the development of cultural products. The development of cultural products needs to be given more space considering that people now more easily consume the results of cultural innovation through various media platforms